2017
DOI: 10.3390/urbansci1030028
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Metropolitan Spatial Structure Evolution: Investigating Spatial Patterns of Employment Growth from 2000 to 2010

Abstract: Urban spatial structure evolution, when using employment as the proxy, can be explained by the change of employment distribution. In this study, we measure the 361 US metro areas (metros) by employment shares, in five submetro sections (i.e., main-center, sub-centers, non-center clusters, non-cluster urban areas, and rural areas), and explore the spatial patterns of submetro growths. We use recognized methods to delimit urban and rural areas, identify employment centers with relative thresholds, and categorize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Lee, B. found that the spatial structure of UAs has a distinct characteristic: The trend of development is from a single center to multiple centers [32]. The studies of other scholars have produced the same results and support this point [33,34]. Fang, C. et al concluded that the stability of the spatial structures of China's UAs is at a relatively low level, and varies greatly from one structure to another [35].…”
Section: Introductionmentioning
confidence: 84%
“…Lee, B. found that the spatial structure of UAs has a distinct characteristic: The trend of development is from a single center to multiple centers [32]. The studies of other scholars have produced the same results and support this point [33,34]. Fang, C. et al concluded that the stability of the spatial structures of China's UAs is at a relatively low level, and varies greatly from one structure to another [35].…”
Section: Introductionmentioning
confidence: 84%
“…Indeed, average density cannot reflect the variations of density and, thus, fails to reflect the urban structure accurately [37,52]. In this way, the validity and interpretability of density indicators often suffer from a lack of-or an unclear-definition of a spatial relationship [53].…”
Section: Density Debate and The Matter Of Scalementioning
confidence: 99%
“…The problem is so vibrant, that the above variables could also be applied in demographic, economic or social aspects, and are directly dependent on the spatial structure which is superior in this case. The discussed problem is currently the research subject for urban sprawl worldwide, concerning the European cities of Barcelona (Roca et al 2004), Rome (Di Zio & Montanari 2010), the capital of South Korea -Seoul (Woo 2014), Moscow (Brade & Rudolph 2004) and metropolitan areas in the USA (Huang et al 2017).…”
Section: Features and Properties Of Suburbanisationmentioning
confidence: 99%